Determinants of Online Purchase Intention: Evidence from Indonesia’s E-Commerce - Dewi Wuisan; Zefanya Hisqia Gedalia; Gabriel Kennard Chan; Benny Aristo; Christoffel Wantah (Universitas Pelita Harapan, 2025)
This study aims to examine the effect of perceived ease of use, perceived usefulness, social influences, price perception, and perceived risk on online purchase intention. The development of internet technology in Indonesia in various sectors is getting faster. One of the industrial sectors that rely on internet technology as a place to do business is e-commerce. Indonesia is one of the countries with the highest percentage of e-commerce users in the world, but the development of e-commerce cannot be separated from the problems that occur. As one of the e-commerce sites in Indonesia, “XYZ” is currently developing its services to make it more attractive to consumers, but there are still many problems that are felt by consumers related to “XYZ”, such as service quality that is not yet optimal. Thus, research is needed regarding the factors that influence online purchase intention. This study uses a quantitative approach with data collection methods using electronic questionnaires distributed through Google Forms. Analysis of the measurement model and structural model in this study was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS 3.0 application. The respondents of this research are Indonesian people who are more than 16 years old and have used “XYZ” e-commerce. The measurement model test consists of testing the validity and reliability, while the measurement model testing consists of testing the coefficient of determination, t -count, significance, and the relationship between constructs. The results of this study indicate that the perceived ease of use variable affects online purchase intention, the perceived usefulness variable affects online purchase intention, the social influences variable affects online purchase intention, and the price perception variable affects online purchase intention. Meanwhile, the perceived risk variable has no effect on online purchase intention.